A Comparative Study of Contemporary Ceramic Sculptures between China and Bangladesh - Md. Anisul Haque (International Journal of Visual and Performing Arts, 2020)
Today, contemporary ceramic sculpture expressions come in various forms. Ceramic sculpture is also a medium to express ideas and creative imagination for ceramic artists. This research paper presents a comparative discussion of Contemporary Ceramic Sculptures between China and Bangladesh, which aims to promote the further development of ceramic sculpture through exchanges of ceramic culture. This research not only analyzes contemporary ceramic sculptures between China and Bangladesh but also learns about the economic, cultural, and social influences of the two countries for the development of global ceramic sculptures. Two countries review the history of ceramics and talk about the specificities in the field of ceramics. This study aims to reveal the development of ceramic sculptures between the two countries so that this research can find out how contemporary ceramic artists in China and Bangladesh created unique and themed ceramics. How modern ceramic sculpture influence by philosophy, culture, tradition, and material effect. The combination of modern china and Bangladeshi ceramic sculpture is so touching and unique. The conclusion of this research is through various experiments and creative learning of ceramic sculptors, making the structure of knowledge of modern ceramic artists become formed. As a result, artistic concepts have become more diverse, and the two countries, Bangladesh and China, can exchange ideas in the creation of ceramic sculptures.